Functional equivalence and evolutionary convergence in complex communities of microbial sponge symbionts - Reynolds, D. (2013)
Microorganisms often form symbiotic relationships with eukaryotes, and the complexity of these relationships can range from those with one single dominant symbiont to associations with hundreds of symbiont species. Microbial symbionts occupying equivalent niches in different eukaryotic hosts may share functional aspects, and convergent genome evolution has been reported for simple symbiont systems in insects. However, for complex symbiont communities, it is largely unknown how prevalent functional equivalence is and whether equivalent functions are conducted by evolutionarily convergent mechanisms. Sponges represent an evolutionarily divergent group of species with common physiological and ecological traits. They also host complex communities of microbial symbionts and thus are the ideal model to test whether functional equivalence and evolutionary convergence exist in complex symbiont communities across phylogenetically divergent hosts. Here we use a sampling design to determine the phylogenetic and functional profiles of microbial communities associated with six sponge species. We identify common functions in the six microbiomes, demonstrating the existence of functional equivalence. These core functions are consistent with our current understanding of the biological and ecological roles of sponge-associated microorganisms and also provide insight into symbiont functions. Importantly, core functions also are provided in each sponge species by analogous enzymes and biosynthetic pathways. Moreover, the abundance of elements involved in horizontal gene transfer suggests their key roles in the genomic evolution of symbionts. Our data thus demonstrate evolutionary convergence in complex symbiont communities and reveal the details and mechanisms that underpin the process.